LANGUAGE ELEMENTS AFFECTING MANIPULATION IN ADVERTISING: LINGUISTIC, SEMANTIC, AND EMPHATIC ELEMENTS - Zumrud Farzaliyeva (International Journal of Innovative Technologies in Social Science, 2023)
Advertising is a tool, without which it would be difficult for our society to develop from the economic point of view. By means of advertisements one can sell his/her products, services and also buy or get whatever he wants. Thus, the role of advertisement is very great in the lives of everybody, beginning from children to elderly ones. Nowadays, advertisements have the biggest power to manipulate customers. The manipulation in different types advertising has become a tool that advertisers use to attract people. It would be just to say that manipulation has moved away the mission of marketing that of meeting the needs of customers and widens the asymmetries of power between the company and the consumer. Some of manipulative advertisements are too difficult to prove because they do have controversial content and nature. In the current article, the main language elements that affect the manipulation process of advertisements are analyzed. To be more exact, three language elements – linguistic, semantic and emphatic elements that manipulate consumers are investigated deeply here. Some unhelpful features of them are also described here, to help future advertisers to avoid ineffective advertisement text or slogans.